ANALISIS PERTUMBUHAN TANAMAN UJI SPESIES MERANTI (Shorea spp) dan KERUING (Dipterocarpus spp) DI IUPHHK-HA PT. ERNA DJULIAWATI KALIMANTAN TENGAH - Abdurrani Muin; Diana Citra Dewi; Reine Suci Wulandari (Jurnal Pemuliaan Tanaman Hutan, 2022)
Meranti is the dominant native species in the IUPHHK-HA PT. Erna Djuliawati in Central Kalimantan. Its use is quite a lot and its existence is dominant as well as a native species, so that this species becomes a top priority in forest development activities in logged-over areas. To get the right species according to the ecological conditions of the site to be planted, PT. Erna Djuliawati conducted a species trial in the IUPHHK-HA area of Central Kalimantan. In the species test plot, the company has planted as many as 20 types of meranti from its own area since 2005. The purpose of this study was to analyze differences in growth and determine the best species in the IUPHHK-HA area. Species trials were carried out using a Randomized Complete Treatment Block Design (RCBD). Parameters measured in this study were total height, diameter, percentage of life and increment of diameter. Based on the analysis results, it turns out that there are differences in growth between 20 species of meranti aged 15 years tested in the species test plot. The fast growing and superior species are Shorea macrophylla, Shorea platyclados and Shorea parvofolia. Other species that can be developed in the IUPHHK-HA area are Shorea johorensis, Shorea johorensis and Shorea stenoptera. Keywords:,Dipterocarpus spp,growth, Shorea spp, species test